Cultural Effect on Financial Literacy (Learn From Wulandoni Barter Market Trader in Lembata Regency) - Petrus Emanuel de Rozari; Hironnymus Jati; Reyner F. Makatita (Syntax Corporation Indonesia, 2022)
The purpose of the study was to understand cultural factors and their influence on the financial literacy of Wulandoni traditional barter market traders in Lembata Regency, East Nusa Tenggara Province. This study uses a qualitative and quantitative approach. Data were collected by observation and in-depth interviews with selected informants. Questionnaires were distributed to 50 barter market traders who were determined randomly to determine the influence of culture on financial literacy using statistical measuring tools. The results showed that the barter market activity decreased from time to time in terms of quantity, quality, and execution time. Market participants who use barter and money systems are increasing. The factor that makes the barter market survive is the reason for the cultural traditions passed down from generation to generation. The traders believe that this tradition should not be violated because it will wreak havoc on them. The financial literacy of traders is in a low category in terms of general knowledge of finance, savings, loans, insurance, and investment. The statistical tests show a significant influence between culture and financial literacy on barter market traders. For this reason, in addition to strengthening cultural traditions, it is necessary to improve the financial literacy and cultural literacy of traders and the community, especially the younger generation, to continue to preserve barter market activities in Wulandoni